Placenta accreta spectrum: biomarker discovery using plasma proteomics - Shainker, Scott A.; Silver, Robert M.; Modest, Anna M.; Hacker, Michele R.; Hecht, Jonathan L.; Salahuddin, Saira; Dillon, Simon T.; Ciampa, Erin J.; D'Alton, Mary E.; Otu, Hasan H.; Abuhamad, Alfred Z.; Einerson, Brett D.; et al. (American journal of obstetrics and gynecology, 2020)
Many cases of placenta accreta spectrum are not diagnosed antenatally, despite identified risk factors and improved imaging methods. Identification of plasma protein biomarkers could further improve the antenatal diagnosis of placenta accreta spectrum . The purpose of this study was to determine if women with placenta accreta spectrum have a distinct plasma protein profile compared with control subjects. We obtained plasma samples before delivery from 16 participants with placenta accreta spectrum and 10 control subjects with similar gestational ages (35.1 vs 35.5 weeks gestation, respectively). We analyzed plasma samples with an aptamer-based proteomics platform for alterations in 1305 unique proteins. Heat maps of the most differentially expressed proteins (T test, P<.01) were generated with matrix visualization and analysis software. Principal component analysis was performed with the use of all 1305 proteins and the top 21 dysregulated proteins. We then confirmed dysregulated proteins using enzyme-linked immunosorbent assay and report significant differences between placenta accreta spectrum and control cases (Wilcoxon-rank sum test, P<.05). Many of the top 50 proteins that significantly dysregulated in participants with placenta accreta spectrum were inflammatory cytokines, factors that regulate vascular remodeling, and extracellular matrix proteins that regulate invasion. Placenta accreta spectrum, with the use of the top 21 proteins, distinctly separated the placenta accreta spectrum cases from control cases (P<.01). Using enzyme-linked immunosorbent assay, we confirmed 4 proteins that were dysregulated in placenta accreta spectrum compared with control cases: median antithrombin III concentrations (240.4 vs 150.3 mg/mL; P=.002), median plasminogen activator inhibitor 1 concentrations (4.1 vs 7.1 ng/mL; P<.001), soluble Tie2 (13.5 vs 10.4 ng/mL; P=.02), soluble vascular endothelial growth factor receptor 2 (9.0 vs 5.9 ng/mL; P=.003). Participants with placenta accreta spectrum had a unique and distinct plasma protein signature.